Towards a Framework for Intelligent Mobile Service Applications - Koch, Fernando (INFOCOMP Journal of Computer Science, 2004)
This paper introduces the Framework for Intelligent Mobile Service, which defines the data structures and computational modules required to support the provisioning of intelligent mobile service solutions.